A national confidential enquiry into community acquired pneumonia deaths in young adults in England and Wales. Issue 12 (1st December 2000) - Simpson, J C G; Macfarlane, J T; Watson, J; Woodhead, M A
Abstract : BACKGROUND: The aim of this study was to describe the frequency, causal pathogens, management, and outcome of a population of young adults who died from community acquired pneumonia (CAP). METHODS: Pneumonia deaths in England and Wales in adults aged 15–44 were identified between September 1995 and August 1996. Patients with underlying chronic illness including HIV infection were excluded. Clinical details for each case were collected from the hospital and general practitioner records. RESULTS: Death from CAP was identified in 27 previously well young adults (1.2 per million population per year). Twenty were known to have consulted a GP for this illness. Nine received antibiotics before hospital admission. A causative pathogen was identified in 17 cases ( Streptococcus pneumoniae in eight). Bacteraemia was present in seven. All patients who reached a hospital ward received antibiotics (69% within two hours of admission). The British Thoracic Society antibiotic guidelines for severe CAP were followed in only 10 cases. Cardiac arrest at home or on arrival at hospital occurred in six cases, one of whom was successfully resuscitated. Of the remaining 21 patients, 71% had two or more markers of severe CAP. All 22 who were admitted reached an intensive care unit, but 11 of these required transfer to another hospital for some aspect of intensive care. One third of patients died within 24 hours of presenting to the hospital. CONCLUSIONS: Death from CAP in previously fit young adults still occurs. While some deaths might be preventable by better patient management, most are unlikely to be preventable by current management practices.